Yusuf al-Qaradawi dan pengaruhnya dalam masyarakat Islam - Mohd Rumaizuddin Ghazali , 1971- (Universiti Sains Islam Malaysia, 2012)
The influence of Yusuf al-Qaradawi's thoughts, a Muslim scholar on Islamic dawah among Muslim community in Malaysia